Mister Miracle - Kirby, Jack 1917-1994; Royer, Mike 1941-; Colletta, Vince 1923-1991 (DC Comics, 2017)
"Spinning off of THE FOURTH WORLD comes JACK KIRBY'S MISTER MIRACLE! As part of the NEW GODS saga, JACK KIRBY'S MISTER MIRACLE focuses on Scott Free's attempt to escape his past and create his own future. Raised on the war-ravaged world of Apokolips, Scott became a master escape artist in order to flee his planet and fight in the epic battle against his former home world's tyrant, Darkseid. Taking on the persona of Mister Miracle and fighting alongside the love of his life, Big Barda, Scott proves that a man, not his upbringing, determines his destiny."...